Thermal performance enhancement in two-phase closed thermosyphon with sandblasted evaporator surface - Kang, Sukkyung; Lee, Seokjin; Lee, Jungho (International Communications in Heat and Mass Transfer, 2024)
To improve the thermal performance of two-phase closed thermosyphon (TPCT), surface modifications such as wet etching, microporous coating, and electrical discharge machining have been applied to the evaporator. These surface modification methods are suitable for lab-scale sample fabrications and experiments but have productivity and economic feasibility limitations for industrial applications such as heat pipe heat exchangers. Sandblasting is a widely used technique that cleans or polishes surfaces by spraying small abrasives with high-pressure air. Since the time required for surface modification is very short and the equipment is not expensive, both productivity and economic feasibility are relatively excellent, which makes it very suitable for industrial applications. We fabricated a sandblasted evaporator using SUS cut-wire abrasives and measured the TPCT performance with a sandblasted evaporator and bare condenser. The evaporator performance was greatly enhanced by increasing the wickability and nucleation site density, whereas the condenser performance slightly deteriorated owing to the increase in film thickness of the liquid condensate. Despite a slight decrease in condenser performance, the thermal resistance of the TPCT was reduced by the sandblasted evaporator. The thermal performance of the entire TPCT was significantly augmented at low heat flux, where the evaporator performance was outstandingly improved.
Keywords: Condenser performance; Economic feasibilities; Electrical discharge machining; Microporous coatings; Performance; Sandblasting; Surface-modification; Thermal Performance; Thermal performance enhancements; Two-phase closed thermosyphon; Sandblasting; Surface modification; Thermal performance; Two-phase closed thermosyphon